2006
DOI: 10.1177/0095798406287109
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Racism and Career Self-Efficacy in African American Adolescents

Abstract: African American adolescents' perceptions of racism and career self-efficacy relationships are examined. Participants in a southwestern urban high school completed the Multigroup Ethnic Identity Measure, Racism and Life ExperiencesScale-Personal and -Group, and career decision and career task self-efficacy scales. Results indicate that participants who perceived a higher degree of racism against their group reported significantly higher self-efficacy for career decision making but not for career task self-effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 64 publications
(98 reference statements)
2
60
1
1
Order By: Relevance
“…In the sample of African American college students, career decision-making self-efficacy was found to be negatively correlated with cultural mistrust. This finding is in contrast to Rollins's (2000) study, which reported that African American adolescents who reported a higher degree of racism against their ethnic group also reported greater self-efficacy for a variety of career decision-making tasks. Career thoughts and cultural mistrust were positively related, supporting Barnes and Lightsey's (2005) and Thompson's (1996) findings that perceived racism is related to intrusive thoughts.…”
Section: Tablecontrasting
confidence: 99%
See 1 more Smart Citation
“…In the sample of African American college students, career decision-making self-efficacy was found to be negatively correlated with cultural mistrust. This finding is in contrast to Rollins's (2000) study, which reported that African American adolescents who reported a higher degree of racism against their ethnic group also reported greater self-efficacy for a variety of career decision-making tasks. Career thoughts and cultural mistrust were positively related, supporting Barnes and Lightsey's (2005) and Thompson's (1996) findings that perceived racism is related to intrusive thoughts.…”
Section: Tablecontrasting
confidence: 99%
“…With regard to career decision-making self-efficacy, Rollins (2000) found that African American adolescents who reported a higher degree of racism against their ethnic group also reported greater self-efficacy for a variety of career decision-making tasks. An additional study found that African American students reported significantly higher career decision-making self-efficacy than did students from other ethnic backgrounds, including Native American, Asian American, and Caucasian American students (Chaney, Hammond, Betz, & Multon, 2007).…”
Section: September 2011 • Volume 59mentioning
confidence: 99%
“…For those persons who were able to complete various levels of schooling, access to employment opportunities that were congruent with their levels of training and ability were virtually nonexistent. Arguably, this trend continues today (Blustein, 2006;King & Madsen, 2007;Rollins & Valdez, 2006). In spite of the discriminatory contexts in which Blacks have lived and still live, they have continued to pursue education and to achieve accomplishments that ought to directly counteract suppositions that they are incapable of academic success.…”
Section: Racial Issuesmentioning
confidence: 99%
“…A study by Rollins and Valdez (2006) provided additional support that ethnic identity is an important factor in the development of career self-efficacy beliefs. In their study of 85 male and female African American 1 lth-and 12'~-grade high school students, the authors found that ethnic identity achievement was related to greater career decisionmaking self-efficacy.…”
Section: Career Decision Self-efficacy (Cdse)mentioning
confidence: 99%
“…& Henry, 1992: Keller, Piotrowski, & McLeod, 1992Luzzo, 1993b). Rollins and Valdez (2006) have found that increasing reports of perceived racism against one's group has been associated with high career decision-making self-efficacy.…”
Section: Impact Of Gendermentioning
confidence: 99%